The re-eutrophication of Lake Erie: Harmful algal blooms and hypoxia - Watson, Susan B.; Miller, Carol; Arhonditsis, George; Boyer, Gregory L.; Carmichael, Wayne; Charlton, Murray N.; Confesor, Remegio; Depew, David C.; Höök, Tomas O.; Ludsin, Stuart A.; Matisoff, Gerald; McElmurry, Shawn P.; et al. (Harmful algae, 2016)
[Display omitted] •Lake Erie is heavily impacted by urban and agricultural nutrient loading.•The timing and bioavailability of these nutrient inputs favour toxic cyanobacteria.•High organic production exacerbates bottom hypoxia and sediment release of phosphorus, which will delay the lake's response to nutrient management.•Modelling has generated soluble and total P reduction targets for Lake Erie.•Many best management options were identified; their performance should be verified on a watershed basis. Lake Erie supplies drinking water to more than 11 million consumers, processes millions of gallons of wastewater, provides important species habitat and supports a substantial industrial sector, with >$50 billion annual income to tourism, recreational boating, shipping, fisheries, and other industries. These and other key ecosystem services are currently threatened by an excess supply of nutrients, manifested in particular by increases in the magnitude and extent of harmful planktonic and benthic algal blooms (HABs) and hypoxia. Widespread concern for this important international waterbody has been manifested in a strong focus of scientific and public material on the subject, and commitments for Canada-US remedial actions in recent agreements among Federal, Provincial and State agencies. This review provides a retrospective synthesis of past and current nutrient inputs, impairments by planktonic and benthic HABs and hypoxia, modelling and Best Management Practices in the Lake Erie basin. The results demonstrate that phosphorus reduction is of primary importance, but the effects of climate, nitrogen and other factors should also be considered in the context of adaptive management. Actions to reduce nutrient levels by targeted Best Management Practices will likely need to be tailored for soil types, topography, and farming practices.